Role of a cyclopentadienyl ligand in Hf precursors using H2O or O3 as oxidant in atomic layer deposition - Song, Youngmin; Kim, Hui Jin; Lee, Soo Hyun; Kwon, Sujin; Shong, Bonggeun; Oh, Il Kwon (Journal of Vacuum Science and Technology A: Vacuum, Surfaces and Films, 2025)
Reducing the gate dielectric thickness in semiconductor devices leads to an increase in leakage current due to tunneling. High-k materials, such as HfO2, are essential in countering this and ensure an adequate equivalent oxide thickness at reduced physical thicknesses. This study investigated atomic layer deposition (ALD) of HfO2 films using the heteroleptic precursor CpHf(NMe2)3 with two different oxidants, H2O and O3, to understand their effects on the growth characteristics, chemical compositional properties, structural properties, and electrical properties. Growth per cycle (GPC) analysis shows that O3 achieved a saturated GPC of 0.85 Å/cycle, whereas H2O exhibits a lower GPC of 0.6 Å/cycle owing to steric hindrance from incomplete Cp ligand removal, leading to higher carbon impurity. X-ray photoelectron spectroscopy revealed an increase in carbon impurity in the H2O-deposited films, supporting these findings. Density functional theory calculations indicated more efficient Cp ligand removal when O3 was used as the oxidant. Furthermore, x-ray diffraction analysis shows that the O3-deposited films had a dominant monoclinic phase after postannealing, whereas the H2O-deposited films exhibited an increase in orthorhombic/tetragonal phases owing to greater carbon concentrations and oxygen vacancy. Electrical characterization of metal-oxide-semiconductor capacitors revealed higher Not values and increased leakage current densities in the H2O-deposited films. These differences are attributed to the higher levels of impurity and oxygen vacancy, which create additional charge-trapping sites and leakage paths. This study underscores the importance of selecting appropriate reactants for ALD to optimize the HfO2 film properties in advanced semiconductor applications.
Keywords: current; Atomic-layer deposition; Carbon impurities; Cp* ligand; Cyclopentadienyl ligands; Deposited films; Gate dielectric thickness; Growth per cycle; HfO 2; Property